Analisis Ketaatan Rumah Sakit Tipe C di Sidoarjo Terhadap Regulasi Pengelolaan Lingkungan Hidup - Rachma Cahyani, Anatasya; Faisal Fadhil, Muhammad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Hospitals, as health service providers, produce liquid medical waste in their operational activities, which if not managed according to standards will result in water pollution. To address this issue, the Sidoarjo government created electronic reporting (SIKOLING) and conducted supervision by creating the SKPL programme. This study was conducted to evaluate the level of obedience and compliance of type C hospitals in Sidoarjo in conducting environmental management reporting and to determine the role of DLHK supervision of water pollution control in accordance with applicable legal regulations. The method used is descriptive qualitative analysis with a quantitative approach. Environmental management carried out by type C hospitals in Sidoarjo experienced a significant increase in 2024 compared to 2023. There are several factors that influence reporting compliance, namely from DLHK supervision and increased understanding from hospitals. For this reason, improvements need to be made from each related party. The purpose of these improvements is to increase reporting compliance so that water pollution can be prevented and environmental quality in Sidoarjo Regency is maintained.